Antiphospholipid antibody-related hepatic vasculitis in a juvenile after non-severe COVID-19: a case report and literature review - Li, Qingyu; Li, Jingya; Zhou, Menglan; Ge, Ying; Liu, Zhengyin; Li, Taisheng; Zhang, Li (Frontiers in Immunology, 2024)
Antiphospholipid antibodies (aPL) are both laboratory evidence and causative factors for a broad spectrum of clinical manifestations of antiphospholipid syndrome (APS), with thrombotic and obstetric events being the most prevalent. Despite the aPL-triggered vasculopathy nature of APS, vasculitic-like manifestations rarely exist in APS and mainly appear associated with other concurrent connective tissue diseases like systemic lupus erythematous. Several studies have characterized pulmonary capillaritis related to pathogenic aPL, suggesting vasculitis as a potential associated noncriteria manifestation. Here we describe a 15-year-old girl who develops hepatic infarction in the presence of highly positive aPL, temporally related to prior non-severe COVID-19 infection. aPLrelated hepatic vasculitis, which has not been reported before, contributes to liver ischemic necrosis. Immunosuppression therapy brings about favorable outcomes. Our case together with retrieved literature provide supportive evidence for aPL-related vasculitis, extending the spectrum of vascular changes raised by pathogenic aPL. Differentiation between thrombotic and vasculitic forms of vascular lesions is essential for appropriate therapeutic decision to include additional immunosuppression therapy. We also perform a systematic review to characterize the prevalence and clinical features of new-onset APS and APS relapses after COVID-19 for the first time, indicating the pathogenicity of aPL in a subset of COVID-19 patients.